Effect of Feeding Zero- or High-Tannin Faba Bean Cultivars and Dehulling on Growth Performance, Carcass Traits and Yield of Saleable Cuts of Broiler Chickens. (23rd September 2019) - Cho, M; Smit, M N; He, L; Kopmels, F C; Beltranena, E
SUMMARY: Color-flowered, high-tannin faba bean (FB ; Vicia faba ) cultivars are more tolerant to frost around harvest time than white-flowered, zero-tannin cultivars. Tannins concentrated on the seed hull reduce both starch and protein digestibility. We therefore evaluated feeding 2 zero-tannin (Snowbird, Snowdrop) or 2 high-tannin (Fabelle, Malik) FB cultivars and the effect of dehulling to reduce tannin content on broiler growth performance, carcass traits, and yield of saleable cuts. Male Ross 708 chicks (n = 585) were fed 1 of 4 FB cultivars either non-dehulled or dehulled in starter (12%, 0–12 d), grower (24%, 13–25 d), and finisher (36%, 26–41 d) mash diets replacing soybean meal (SBM) and wheat grain (control diet). Overall, daily feed intake was greatest for Snowbird and Fabelle, and lowest for Malik; Snowdrop was intermediate. Daily weight gain was greater for Fabelle than other cultivars, and greater for control than FB cultivars. Gain-to-feed ratio (G:F ) was greatest for Fabelle but lowest for Snowbird; Snowdrop was not different from Fabelle or Malik, and Malik was not different from Snowbird. Broiler G:F and chilled carcass weight were greater for controls than FB cultivars. Breast meat yield (BMY) was greater for Snowbird, and lower for Fabelle; Malik was not different from Snowbird or Snowdrop; Snowdrop was not different from Fabelle. Dehulling FB lowered BMY. Feeding broilers low-vicine/convicine high-tannin Fabelle resulted in slightly better growth performance but lower BMY than feeding zero-tannin cultivars or high-tannin Malik. Dehulling FB did not improve broiler growth performance or carcass dressing to the level of controls fed SBM-wheat only.